THE SMART ASN APPLICATION FOR INTEGRATING PERSONNEL SERVICES AT THE REGIONAL CIVIL SERVICE AGENCY OF SIDOARJO REGENCY - Sandrin, Kristie Ferlita; Hertati, Diana (Institut Pendidikan Indonesia, 2025)
The implementation of information technology in public services, particularly through E-Government, serves as a strategic step to enhance government efficiency, transparency, and accountability. Sidoarjo Regency, as part of the implementation of the Electronic-Based Government System (SPBE), has developed the Smart ASN application to manage personnel data in a more integrated and efficient manner. This study aims to analyze the innovation of the Smart ASN application and its impact on the quality of personnel services in Sidoarjo Regency using Rogers' theory. The research employs a qualitative descriptive approach, collecting data through observation and literature review. Findings reveal that the Smart ASN application has successfully improved efficiency in personnel data management by reducing data redundancy, accelerating updates, and facilitating access for State Civil Apparatus (ASN). Additionally, transparency and accountability have increased, as data can be monitored in real-time. However, challenges include a technological knowledge gap among ASNs and resistance to change. The results of this study indicate that the Smart ASN application has a positive impact on improving the quality of public services in Sidoarjo Regency, although further improvements are needed in training and technology dissemination for State Civil Apparatus (ASN).